Evaluating the Impact of Emotional Intelligence on Human Resource Productivity among Managers and Supervisors of National Housing Projects in Qom: The Mediating Role of Organizational Trauma - Attarnia, Zahra; Nazarpour, Mohammad Taghi (Management Strategies and Engineering Sciences, 2026)
In today’s highly challenging environment, human resource productivity, as one of the key components of organizational success, is significantly influenced by soft skills, particularly emotional intelligence. In project-oriented environments such as construction projects, the role of managers and supervisors in maintaining employee motivation, efficiency, and psychological well-being is critically important. The present study aimed to evaluate the impact of emotional intelligence on the human resource productivity of managers and supervisors involved in the National Housing Projects in Qom, with an emphasis on the mediating role of organizational trauma. The present research was applied in terms of purpose and descriptive-survey in terms of data collection method. The statistical population consisted of all managers and supervisors of the National Housing Project workshops in Qom, among whom 154 individuals were selected as the sample size using Cochran’s formula and simple random sampling. Data collection instruments included the Emotional Intelligence Questionnaire developed by Schutte et al. (1998), the Human Resource Productivity Questionnaire by Hersey and Goldsmith (1980), and the Organizational Trauma Questionnaire developed by Vivian and Horman (2015). The content validity of the questionnaires was confirmed by a panel of experts and managers from the Engineering Organization. Reliability was assessed using Cronbach’s alpha coefficient through SPSS version 26, and all coefficients were calculated above 0.70. The results obtained through PLS software indicated that emotional intelligence has a significant effect on the human resource productivity of managers and supervisors in the National Housing Projects of Qom through the mediating role of organizational trauma. Emotional intelligence also significantly affects both human resource productivity and organizational trauma among managers and supervisors of the National Housing Project workshops in Qom. Furthermore, organizational trauma significantly affects human resource productivity among these managers and supervisors. Therefore, it is recommended that organizations implement emotional intelligence training and crisis management programs in order to provide an appropriate foundation for improving human resource performance.